PHILOSOPHICAL AND LEGAL FOUNDATIONS OF ENVIRONMENTAL LAW: CONTRIBUTIONS FROM CLASSICAL AND CONTEMPORARY THINKERS - de Giorge Cerqueira, Homero (Revista Gênero e Interdisciplinaridade, 2025)
This article addresses the philosophical and legal foundations of Environmental Law, exploring the contributions of classical and contemporary thinkers who have enriched the debate on environmental protection. With the advancement of ethics and legal thought, several works have gained prominence, such as those of Hans Jonas, who emphasizes responsibility towards future generations; Ronald Dworkin, who discusses the normative force of legal principles applicable to the environment; and Ulrich Beck, who investigates the challenges imposed by modernity and the need for effective policies to mitigate ecological impacts. A critical analysis of the thinking of these and other authors, such as Jürgen Habermas and Hans Kelsen, reveals a gap in the practical application of their principles in the formulation of environmental policies and standards. This study proposes a reflection on the translation of philosophical concepts into robust legal guidelines, highlighting the relevance of intergenerational responsibility and the mechanisms of legal coercion in the scope of environmental law. By exploring these dimensions, the article seeks to contribute to a solid theoretical basis that supports the effective protection of the environment in contemporary times.